2020
DOI: 10.1148/radiol.2020200478
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based Bosniak Classification of Cystic Renal Masses, Version 2019: Interobserver Agreement, Impact of Readers’ Experience, and Diagnostic Performance

Abstract: T he Bosniak classification of cystic renal masses (CRMs) has contributed substantially to the stratification of malignancy risk in the 3 decades since it was proposed (1). As a living system, refinements were made in 1993 and 2005 (version 2005) (2-4). With the current version of the Bosniak classification (version 2005), several shortcomings in both clinical practice and scientific research have been noted. A systematic review has suggested that interreader variability for the Bosniak classification is large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 23 publications
(22 reference statements)
1
28
0
Order By: Relevance
“…Preliminary studies evaluating interobserver agreement while using Bosniak Classification, version 2019 show moderate (MRI) to substantial (CT and MRI) agreement between readers. However, data are limited by a small sample size (11,12,15) Lack of explicit definitions for imaging terms and features contributed to a third shortcoming: widely variable reported malignancy rates for each of the Bosniak classes (4-7). A fourth shortcoming of the original classification was that MRI and US were not fully incorporated.…”
Section: Imaging Techniques For Evaluation Of Cystic Renal Masses General Imaging Techniquementioning
confidence: 99%
“…Preliminary studies evaluating interobserver agreement while using Bosniak Classification, version 2019 show moderate (MRI) to substantial (CT and MRI) agreement between readers. However, data are limited by a small sample size (11,12,15) Lack of explicit definitions for imaging terms and features contributed to a third shortcoming: widely variable reported malignancy rates for each of the Bosniak classes (4-7). A fourth shortcoming of the original classification was that MRI and US were not fully incorporated.…”
Section: Imaging Techniques For Evaluation Of Cystic Renal Masses General Imaging Techniquementioning
confidence: 99%
“…In our study, intra-observer agreement was similar for both systems within readers and the degree of agreement between the two systems did not substantially change at either session for any reader. A moderate level of agreement using Bosniak classification has been reported previously using both the original and v2019 systems (3,8). This level of agreement is not optimal; however, implications on clinical care are not directly correlated to agreement.…”
mentioning
confidence: 68%
“…Among many changes, Bosniak.v2019 aims to improve inter-observer agreement compared to Bosniak.original through rigorous definitions of imaging features and Bosniak classes (1). Preliminary studies comparing inter-observer agreement between the two classification systems published to date have shown either no difference or only modest improvement (2)(3)(4). Recently published support aids for use of Bosniak.v2019, including diagrammatic and online decision support aim to simplify use of Bosniak.v2019 (5) but the impact of these decision support aids have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…While the Bosniak classification was originally developed for contrast-enhanced CT, the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) proposed a CEUS-adapted Bosniak categorization system in 2020 in order to overcome differences in imaging specifics and improve the diagnostic accuracy of CEUS in characterizing cystic renal lesions [33]. A recent study evaluating the impact of the updated Bosniak classification in MRI demonstrated higher interobserver agreement and higher diagnostic accuracy when using the updated version [34]. All in all, the Bosniak classification system is a useful tool to make radiologic reporting more standardized and structured, thus facilitating further patient management.…”
Section: Discussionmentioning
confidence: 99%